A new approach to optimal smooth path planning of mobile robots with continuous-curvature constraint. Issue 1 (1st January 2021) - Xu, Lin; Song, Baoye; Cao, Maoyong
ABSTRACT: Smooth path planning is very important to mobile robots with continuous-curvature constraint, but there are still some limitations and drawbacks on traditional planning approach. To deal with this problem, a new approach combined with parametric cubic Bezier curve (PCBC) and particle swarm optimization with adaptive delayed velocity (PSO-ADV), is developed to plan the smooth path of mobile robots. Unlike the traditional smooth path consisting of several linear and curve segments with discontinuous curvature at the joints, the smooth path composed of PCBC segments has equivalent curvature at the segment joints, thereby it is able to attain continuous curvature along the whole smooth path. In terms of the mathematical formulation of PCBC, the smooth path planning is essentially an optimization problem to seek the optimal control points and parameters of PCBC segments. To handle this intractable problem and some frequently encountered troubles (e.g. premature convergence and local trapping), a new PSO-ADV algorithm is developed by blending the term of adaptive delayed velocity, and its superiority can be confirmed by several simulation experiments. The new approach is finally applied to produce the smooth path with continuous-curvature constraint, and can achieve superior performance in comparison with traditional method.